Fahr Syndrome and Syncope: Case Report and Clinical Radiological Characteristics - Avellaneda, Luis; Rojas, Marco; Torres, Karen; Cetina, Luis; Vargas, Ledmar (International Clinical Neuroscience Journal, 2022)
Background: Fahr´s syndrome is a rare neurodegenerative entity, which consists of calcifications of the basal ganglia and cerebrospinal nuclei, which can be associated with neurological and neuropsychiatric symptoms. However, the difference between syndrome and Fahr’s disease is highlighted. Case Report: a 55-year-old man with underlying thyroid disease undergoing treatment, debuted with syncope with posterior cranial trauma, which was admitted to the emergency service, performing imaging studies with findings compatible with Fahr´s syndrome. Conclusion: syncope as a cardiac symptom in a patient with Fahr syndrome, metabolic and structural abnormalities ruled out must be.